Minting NFTs on OpenSea Marketplace - Savia, Melyssa; Troka, Leonard (International Journal of Art, Design, and Metaverse, 2023)
This study examines the risk and return characteristics of the NFT-based artists, creators, and creators the cryptocurrency exchange. This study is motivated by the recent surge in the NFT activity on the part of creators, investors, and traders. We begin by proposing novel classification of the existing NFTs that range from NFT blockchains through NFT metaverse to NFT DeFi. Next, It focuses on minting NFT in OpenSea. The method includes (1) Set up a crypto wallet, (2) Create a collection, and (3) Upload the work. In the final analysis of the paper, we find that NFT infrastructure integrated within the existing blockchains increase market valuations of these networks. The NFT industry represents another important use case for blockchains, in addition to artists, creators, and collectors to trade easily.